2013
DOI: 10.1271/bbb.130404
|View full text |Cite
|
Sign up to set email alerts
|

Transport Mechanisms for Soy Isoflavones and Microbial Metabolites Dihydrogenistein and Dihydrodaidzein Across Monolayers and Membranes

Abstract: Isoflavone data concerning the metabolism and permeability on intestinal epithelial cells are scarce, particularly for microbial isoflavone metabolites. This study evaluates the absorption mechanisms for the isoflavones, genistein and daidzein, and their microbial metabolites, dihydrogenistein (DHG) and dihydrodaidzein (DHD). The permeability characteristics of isoflavones were compared by using the Caco-2 human colon adenocarcinoma cell line for a parallel artificial membrane permeability assay, and comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 35 publications
(50 reference statements)
1
32
0
1
Order By: Relevance
“…The transepithelial transport experiment was performed as described previously (Kobayashi et al, 2007(Kobayashi et al, , 2013. Briefly, cells were cultured normally in 75-cm …”
Section: Glucose Transport Measurements In Caco-2 Cells Caco-2 Cellsmentioning
confidence: 99%
“…The transepithelial transport experiment was performed as described previously (Kobayashi et al, 2007(Kobayashi et al, , 2013. Briefly, cells were cultured normally in 75-cm …”
Section: Glucose Transport Measurements In Caco-2 Cells Caco-2 Cellsmentioning
confidence: 99%
“…In Caco-2 monolayers, the BCRP specific inhibitor, FTC (1 μM) decreased the efflux ratio of genistein by 3-fold, confirming that genistein is actively transported by BCRP in the BL-to-AP direction [95]. BCRP-mediated transport of genistein in Caco-2 cells was confirmed in another study which demonstrated that the BCRP inhibitor, estrone-3-sulfate increased the permeability of genistein by 40% in these cells [96]. .…”
Section: Evidence For Isoflavones As Substrates Of Bcrpmentioning
confidence: 79%
“…The preference for BL-to-AP transport was abolished by the BCRP specific inhibitor, fumitremorgin C (FTC, 3 μM), further confirming a critical role for BCRP in the transcellular transfer of genistein [71]. Since this initial report, a number of studies have characterized the bidirectional transport of genistein in other BCRP-overexpressing (i.e., Madin-Darby canine kidney II; MDCK/BCRP) and endogenously expressing (i.e., Caco-2) cell lines [69, 95, 96]. Similar to the LLC/BCRP cells, the BL-to-AP transport of genistein (as quantified by LC/MS) was favored in the MDCK/BCRP cells with a efflux ratio that was 2-fold higher in the overexpressing cells as compared to the empty vector cells that lacked BCRP protein [69].…”
Section: Evidence For Isoflavones As Substrates Of Bcrpmentioning
confidence: 94%
“…1). The reported isoflavone metabolites were utilized for various metabolomic studies to investigate correlations among host physiology, host metabolism, and gut microbiota changes (Lee et al 2012;Kobayashi et al 2013). The genes involved in the biotransformation of daidzein and the metabolites were also cloned from the isolated intestinal bacteria for the biochemical research (Shimada et al 2010;Tsuji et al 2012;Schröder et al 2013).…”
Section: Discussionmentioning
confidence: 99%